The mediating role of self-efficacy between workplace violence and PTSD among nurses in Liaoning Province, China: A cross-sectional study - Lu, Jiachen; Yu, Yingying; Wang, Bin; Zhang, Yanni; Ji, Haoqiang; Chen, Xu; Sun, Meng; Daun, Yuxin; Pan, Yuanping; Chen, Yunting; Yi, Yaohui; Dou, Xiaofeng; et al. (Frontiers in Psychology, 2023)
Nurses are at high risk for workplace violence in the workplace, which can lead to psychological problems. The purpose of this study was to determine the relationship between workplace violence, self-efficacy, and PTSD, and to further explore whether self-efficacy mediates the relationship between workplace violence and PTSD among Chinese nurses.